Correlation of mathematical resilience, attitudes and learning habits, gender and their impact on student academic performance - Fatimah, Ade Evi; Siagian, Muhammad Daut; Rini Sulastri (Jurnal Elemen, 2025)
Students enrolled in Informatics Engineering Education programs frequently encounter substantial obstacles in mastering Discrete Mathematics, a fundamental subject that necessitates perseverance, logical reasoning, and effective study strategies. These challenges are often compounded by negative perceptions of mathematics, lack of perseverance in learning, and ineffective study habits. In this context, it is imperative to investigate non-cognitive factors that may influence students’ academic performance (SAP), such as mathematics resilience (MR), attitudes and learning habits (ALH), and gender. This study endeavours to examine the extent to which MR, ALH, and gender contribute to SAP in Discrete Mathematics. A quantitative ex post facto correlational design was employed, involving a sample of 50 third-semester students selected through proportional random sampling methods. Data were collected using standardised questionnaires assessing MR and ALH, along with academic records from the targeted course. The findings indicate that both MR and ALH significantly influence students’ academic performance. Among these factors, ALH emerged as the most influential contributor to academic success. In contrast, gender did not have any substantial impact on students’ achievement. These results emphasize the significance of non-cognitive factors—particularly resilience and effective learning behaviors—in supporting students’ success in mathematics-related coursework.